Smoking Behavior Study on Teenagers’ - Virdiana Ramadhani; Anas Hidayat (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2009)
This study aims to determine the role of peers' influence, attitude towards cigarette advertising, and attitude towards smoking behavior on teenagers’ smoking intention. The respondents in this study were 150 students of high schools in Yogyakarta city. Quantitative data analysis methods used to test three hypotheses in this study is a Multiple Re-gression Analysis. Findings found that there are only two variables that have positive relation towards teenagers’ smoking intention, i.e. peers' influences and attitude towards smoking be-havior. Attitude towards cigarette advertising do not positively contribute for teenagers to have an intention to smoke. Keywords: Peers’ Influence, Attitude towards Cigarette Advertising, Attitude towards Smoking Behavior, Teenagers’ Smoking Intention